Structural geological 3D-model combining geophysical surface measurements and borehole data at the Kopparnäs site, S Finland - Muurinen, Miikka (My University, 2026)
The study of faults and fracture systems within crystalline bedrock has become a major point of interest in recent years. Traditional methods such as field mapping and remote sensing have certain limitations regarding for example assessment of horizontally oriented structures and survey depth penetrations. Therefore, alternative methods are needed to assess horizontal fracturing and their three-dimensional attributes. The purpose of this study is to model fracturing at the Kopparnäs study site in southern Finland with the focus on the horizontal fracturing and the geometrical attributes of fracturing, such as sizes, orientations, intensity and variance in depth. The study acts as groundwork for further investigations regarding for example DFN- and fluid flow modelling. In this work, a joint use of surface gathered- and subsurface geophysical data was employed. The surface gathered data consists of a set of structural field measurements, 6 ERT survey lines and 9 GPR survey lines. The borehole R307 was used for collecting subsurface information which included OBI/ABI images, numerical fracture data derived from OBI/ABI images and a BHGPR image conducted from the borehole. In addition, open-source aeromagnetic maps and digital elevation models were used. Fracture traces from crosscutting and parallel running GPR survey lines were linked to form three dimensional horizontal to subhorizontal planes representing fracture surfaces. In total 47 horizontal fracture planes were created in 7 clusters. Field measurements near the clusters were extruded to planes representing upright fracturing. In addition, three major fault planes were identified and modelled. Numerical fracture data from borehole R307 was linked with fracture traces based on the BHGPR image to produce a fracture set with determined fracture geometries in depth. The joint methods in this study proved adequate for i) modelling approximations of fault plane geometries ii) identifying and imaging horizontal fractures in homogenous surface layer bedrock, iii) 3D modelling horizontal fracture surfaces with quantified geometries, iv) imaging strongly reflecting discrete fractures and fracture zones in depth and v) determining the geometries of these fractures and modelling them as 3D surface. This thesis provides a workflow for incorporating often excluded hydraulically conductive horizontal fractures into structural 3D models and a method for increasing depth penetration of fracture network analysis. These results can be used to increase the accuracy of deterministic 3D fracture system characterization in the future.

Kiteisen kallioperän siirrosten ja rakosysteemien tutkiminen on muodostunut tärkeäksi kysymykseksi viime vuosien aikana. Perinteisillä kenttä- ja kaukokartoitusmenetelmillä on tietyt rajoitteet liittyen esimerkiksi vaaka-asentoisten rakenteiden tutkimiseen ja tutkimusten syvyystarkkuuteen. Kun halutaan tutkia vaaka-asentoisia rakenteita ja niiden kolmiulotteisia ominaisuuksia, on käytettävä vaihtoehtoisia metodeja. Tämän tutkimuksen tavoite on mallintaa rakoilua Kopparnäsin tutkimusalueella eteläisessä suomessa. Tutkimuksessa keskitytään vaaka-asentoisiin rakoihin ja niiden geometrisiin ominaisuuksiin, kuten koko-, suunta-, intensiteetti- ja syvyysjakaumaan. Tutkimuksen tuloksia on tarkoitus käyttää esimerkiksi DFN- ja fluidien virtauksen mallinnukseen tulevaisuudessa. Työssä on käytetty maan pinnalta ja maan alta kerättyä geofysikaalista aineistoa. Pinta-aineistoon kuuluu kentällä tehtyjä rakomittauksia, kuusi ERT-mittauslinjaa ja yhdeksän GPR-mittauslinjaa. Kairareiästä R307 kerätty maanalainen aineisto sisältää OBI/ABI kuvat, edellä mainituista johdettu numeerinen rakodata ja reiästä otettu BHGPR kuva. Lisäksi apuna on käytetty avoimena saatavilla olevaa aineistoa, kuten aeromagneettista karttaa ja digitaalista korkeusmallia. Leikkaavien ja vierekkäisien GPR linjojen rakoviivatulkintoja linkitettiin yhteen ja niistä muodostettiin tasoja, jotka edustavat vaaka-asentoisia rakopintoja. Tuloksena oli kaikkiaan 47 rakopintaa, jotka ovat jaettuna seitsemään eri alueelliseen ryhmään. Näiden ryhmien alueella sijaitsevat kenttämittaukset tursutettiin pinnoiksi edustamaan pystyasentoista rakoilua. Lisäksi kolme suurempaa siirrospintaa havaittiin ja mallinnettiin. Numeerinen rakodata R307 kairareiästä linkitettiin BHGPR kuvan kanssa, minkä avulla kairareiästä saatiin tulkittua rakosetin geometriset ominaisuudet. Tutkimuksessa käytettyjen menetelmien avulla pystyttiin i) mallintamaan arvioita siirrospintojen geometrioista, ii) havaitsemaan ja mallintamaan vaakatasoisia rakoja homogeenisen kallioperän pintakerroksissa, iii) mallintamaan rakopintoja ja määrittämään niiden geometrisia ominaisuuksia, iv) kuvantamaan voimakkaasti heijastavia rakoja ja rakovyöhykkeitä syvällä ja iv) määrittämään näiden rakojen geometriset ominaisuudet ja mallintamaan ne pintoina. Tämä työ esittelee tavan, jolla voidaan lisätä rakennegeologisiin 3D-malleihin usein pois jätetyt vettä johtavat vaakaraot ja menetelmän, jolla voidaan lisätä rakosysteemien tutkimisen syvyystarkkuutta. Näitä tuloksia voidaan käyttää tulevaisuudessa determinististen 3D-rakomallien tarkkuuden parantamisessa.
Keywords: bedrock structures, fracture network, ground penetrating radar, borehole radar, geological 3D model, subhorizontal fractures, kallioperän rakenteet, rakoverkko, maatutka, kairareikätutka, geologinen 3D malli, vaakaraot